TOTAL OIL CONTENT AND EPIPHYTIC DIATOM DENSITY IN SEAGRASS LEAVES Enhalus acoroides AT PANDARATAN BEACH TAPANULI TENGAH REGENCY NORTH SUMATERA PROVINCE - Puspita, Sarah; Siregar, Sofyan; Nedi, Syahril (Asian Journal of Aquatic Sciences, 2021)
The aimed of this study was to determine the total oil content at Pandaratan Beach, determine epiphytic diatoms density in seagrass leaves Enhalus acoroides at Pandaratan Beach, and determined the relationship between total oil content and epiphytic diatoms density in seagrass leaves E. acoroides at Pandaratan Beach. Based on the results of research conducted, the highest total oil content is in the area around the sea transportation route, namely 0.25 ppm and the lowest total oil content is in areas far from human activity, namely 0.16 ppm. The highest epiphytic diatoms density found in areas far from human activities, namely 932.21 Ind/cm2 and the lowest epiphytic diatoms density found in the area around the sea transportation lines, namely 663.41 Ind/cm2.The relationship between total oil content and epiphytic diatoms density at Pandaratan Beach, Tapanuli Tengah Regency, North Sumatra Province has a very weak relationship (r = 0.03).